Fashion Design for Sustainability Teaching Project: : action in 2019 at IFRS campus Erechim (Revista de Ensino em Artes, Moda e Design, 2020)
The clothing industry presenting chemical and social impacts throughout its cycle. Thus,environmental awareness about these impacts as well as their confrontation is urgent amongprofessionals in the area. In view of this scenario, this paper aims to present the conceptionand action of the Fashion Design for Sustainability Teaching Project throughout 2019 at IFRScampus Erechim. For that, it uses the experience report as a method, exposing the context ofcreation, the procedures used and the actions implemented throughout the project. As a result,the project provided an approximation between the disciplines of courses in the Fashionarea and the theme design for sustainability, fostering the environmental awareness of futureprofessionals.